Dietary patterns during pregnancy and the association with sociodemographic characteristics among women attending general practices in southern Brazil: the ECCAGe Study Padrones alimentarios en la gestación y su asociación con características sociodemográficas en mujeres atendidas en unidades básicas de salud en el sur de Brasil: estudio ECCAGe Padrões alimentares na gestação e associação com características sociodemográficas em mulheres atendidas em unidades básicas de saúde no Sul do Brasil: Estudo ECCAGe - Rafael Marques Soares; Patrícia Manzolli; Michele Drhemer; Caroline Buss; Cristiane Melere; Silvia Giselle Ibarra Ozcariz; Maria Inês Schmidt; Maria Teresa Anselmo Olinto; Suzi Camey; Juliana Feliciati Hoffmann; Maria Angélica Antunes Nunes; Andréa Poyastro Pinheiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The assessment of the relationship between food intake and sociodemographic factors is crucial for developing effective public health policies. The present study aimed to examine dietary patterns in pregnant women and the association between these patterns and sociodemographic characteristics. Pregnant women attending general practices in southern Brazil (n = 712) answered a questionnaire and a food-frequency questionnaire with 88 items. Three dietary patterns were identified using cluster analysis. The association between the dietary patterns and sociodemographic variables was analyzed using the chi-square test and adjusted standardized residuals (p < 0,05). The restricted pattern was associated with lower maternal age, not living with a partner and being a non-working student. The varied pattern was associated with older maternal age, living with a partner, being employed and higher levels of education and income. The common-Brazilian dietary pattern included traditional Brazilian food items and was associated with lower levels of education and income, being unemployed and being a non-student. La evaluación del consumo alimentario y de las condiciones sociodemográficas es crucial para el desarrollo de políticas públicas. Este estudio examinó padrones alimentarios en gestantes y su asociación con características sociodemográficas. Las gestantes (n = 712) atendidas en unidades básicas de salud en el sur de Brasil, respondieron a un cuestionario sobre características sociodemográficas y a un cuestionario de frecuencia alimentaria. Se identificaron tres padrones alimentarios por análisis de clúster. A través del test chi-cuadrado ajustado con residuos se verificó la asociación de los padrones alimentarios con las variables sociodemográficas (p < 0,05). El padrón restringido fue asociado con gestantes más jóvenes, que no viven con un compañero y sólo estudian; el padrón variado con mujeres más viejas, que viven con compañero, trabajan y tienen niveles de escolaridad y renta más altos. Mujeres que no trabajan ni estudian, y poseen niveles de renta y escolaridad más bajos, estuvieron asociadas al padrón común-brasileño, caracterizado por alimentos tradicionales de la población brasileña. A avaliação do consumo alimentar e das condições sociodemográficas é crucial para o desenvolvimento de políticas públicas. Este estudo examinou os padrões alimentares em gestantes e sua associação com características sociodemográficas. Gestantes (n = 712) atendidas em unidades básicas de saúde no sul do Brasil, responderam a um questionário sobre as características sociodemográficas e a um outro de frequência alimentar. Foram identificados três padrões alimentares por análise de cluster. Utilizando-se o teste qui-quadrado com resíduos ajustado verificou-se a associação dos padrões alimentares com as variáveis sociodemográficas (p < 0,05). O padrão restrito foi associado com gestantes mais jovens, que não moram com o companheiro e só estudam; o padrão variado com mulheres mais velhas que moram com o companheiro, trabalham e têm níveis de escolaridade e renda mais altos. Mulheres que não trabalham nem estudam e possuem níveis de renda e escolaridade mais baixos estiveram associadas ao padrão comum-brasileiro, caracterizado por alimentos tradicionais da população brasileira.